Effect Of Problem-Based Learning On Health Resilience And Self-Efficacy Of Junior High School Adolescents In Reproductive Health Behavior And Personal Hygiene - Dewa Gede Firstia Wirabrata; Ni Made Swasti Wulanyani; Nice Maylani Asril; Dewa Bagus Sanjaya (Lembaga Bale Literasi, 2026)
The fundamental problems experienced by adolescents are low resilience and minimal self-efficacy, in addition there is a tendency to separate cognitive (knowledge) and psychological such as resilience and self-efficacy, so that a pedagogical formula has not been found that is able to integrate both in the context of reproductive health and personal hygiene. Therefore, this study aims to analyze the effect of Problem Based Learning on Health Resilience and Self-Efficacy of Junior High School Adolescents in Reproductive Health Behavior and Personal Hygiene. This study uses a quantitative approach with a quasi-experimental posttest-only control group design. The population in the study was all students of Undiksha Laboratorium Junior High School totaling 52 people. The sampling technique used was saturated sampling which was divided into two groups, namely class 7A experimental group and class 7B control group. The research instrument consisted of a health resilience and self-efficacy questionnaire. Data analysis techniques consisted of prerequisite tests: normality, homogeneity, box's M, and multicorrelation. Hypothesis testing consisted of: ANOVA and MANOVA tests. The results of the one-way ANOVA test obtained an F value of 39.943 and a significance value of 0.001, which means there is an influence of problem-based learning on adolescent health resilience. Furthermore, the one-way ANOVA test of self-efficacy obtained an F value of 51.111 and a significance value of 0.001 <0.05, which means there is an influence of problem-based learning on adolescent self-efficacy. The results of the multivariate test analysis of health resilience and self-efficacy data in the Pillai's trace, Wilks's lambda, and Hotelling's trace columns, and Roy's Langest root obtained an F value of 49.000 and a significance value of 0.001 <0.05, which means there is a significant influence of Problem-Based Learning on health resilience and self-efficacy of junior high school students in the learning material of reproductive health behavior and personal hygiene.